The Effect of Silver, Zinc Oxide, and Titanium Dioxide Nanoparticles Used as Final Irrigation Solutions on the Fracture Resistance of Root-Filled Teeth - Jowkar Z; Hamidi SA; Shafiei F; Ghahramani Y (Dove Medical Press, 2020)
Zahra Jowkar,1 Seyed Ahmadreza Hamidi,2 Fereshteh Shafiei,1 Yasamin Ghahramani3 1Oral and Dental Disease Research Center, Department of Operative Dentistry, School of Dentistry, Shiraz University of Medical Sciences, Shiraz, Iran; 2Department of Operative Dentistry, School of Dentistry, Shiraz University of Medical Sciences, Shiraz, Iran; 3Department of Endodontics, School of Dentistry, Shiraz University of Medical Sciences, Shiraz, IranCorrespondence: Fereshteh Shafiei Tel +98 71-36263193Email shafief@sums.ac.irAim: This study was conducted to evaluate the effect of three nanoparticle solutions used as final root canal irrigants on the fracture resistance of endodontically treated roots.Materials and Methods: Sixty intact single-rooted premolar teeth were used after removing the crowns below the cementum–enamel junction to standardize the length of the remaining roots to 13 mm. After instrumenting the roots using ProTaper Universal rotary instruments up to size F4, the roots were randomly divided into six groups (n=10) according to the final irrigating solutions: Group 1: normal saline; Group 2: 2% chlorhexidine (CHX); Group 3: 17% EDTA+2.5% NaOCl; Group 4: 17% EDTA+0.1% silver nanoparticle (SNP) solution; Group 5: 17% EDTA+0.1% titanium dioxide nanoparticle (TNP) solution; Group 6: 17% EDTA+0.1% zinc oxide nanoparticle (ZNP) solution. After filling the root canals with gutta-percha and AH Plus sealer, the fracture resistance (FR) values were measured. The data were subjected to the one-way analysis of variance and the Tamhane post hoc test (p=0.05).Results: EDTA + NaOCl had the lowest FR value, followed by normal saline and CHX (p values < 0.05). No significant difference was found between the FR of roots irrigated with CHX and normal saline (p > 0.05). The application of nanoparticles (SNP, TNP, and ZNP) was associated with a significantly greater FR than that of other irrigation solutions (p values < 0.05).Conclusion: The final irrigation of root canals with nanoparticles enhanced the fracture resistance of the endodontically treated roots. The lowest FR value was observed for NaOCl.Keywords: fracture resistance, nanoparticles, root canal irrigants